Proper housing conditions in experimental stroke studies—special emphasis on environmental enrichment - Mering, Satu; Jolkkonen, Jukka (Frontiers in Neuroscience, 2015)
Environmental enrichment provides laboratory animals with novelty and extra space, allowing different forms of multisensory stimulation ranging from social grouping to enhanced motor activity. At the extreme end of the spectrum, one can have a super-enriched environment. Environmental enrichment is believed to result in improved cognitive and sensorimotor functions both in naïve rodents and in animals with brain lesions such as those occurring after a stroke. Robust behavioral effects in animals which have suffered a stroke are probably related not only to neuronal plasticity in the perilesional cortex but also in remote brain areas. There is emerging evidence to suggest that testing restorative therapies in an enriched environment can maximize treatment effects, e.g., the perilesional milieu seems to be more receptive to concomitant pharmacotherapy and/or cell therapy. This review provides an updated overview on the effect of an enriched environment in stroke animals from the practical points to be considered when planning experiments to the mechanisms explaining why combined therapies can contribute to behavioral improvement in a synergistic manner.